Officially-Supported Export Credits : Developments and Prospects, 1988. (World Economic and Financial Surveys; World Economic and Financial Surveys, 1987)
This paper emphasizes on the policy reaction of the agencies and their authorities to countries in various stages of debt-servicing difficulties. It was found that, largely for competitive reasons and provided that significant arrears had not emerged, agencies as a group had tended to remain quite open for debtors pursuing policies that could be expected to lead to payments difficulties, thus facilitating the postponement of necessary adjustment by the debtor and increasing the likelihood of eventual debt-servicing difficulties. Despite this more open stance, the volume of new medium-term credit and cover commitments to developing countries appears to have fallen off sharply over the past two years. Although for some debtors the operative constraint is clearly on the supply of new credits and cover, this is not the general case and, indeed, agencies reported net repayments from some countries for which they were wide open for new business.